Penciri Kemiskinan Ekstrem di 35 Kabupaten Prioritas Penanganan Kemiskinan Ekstrem - Nuri Taufiq (Seminar Nasional Official Statistics, 2022)
The government is currently targeting extreme poverty by 2024 to reach 0 percent. This achievement target is 6 years faster than the SDGs target. In 2021, extreme poverty alleviation efforts will be focused on 7 provinces and prioritized on 35 districts. Efforts are needed to accelerate the handling of extreme poverty, one of which is to sharpen the database to achieve target accuracy. Recognizing how the characteristics of extreme poor households are an important part of efforts to improve databases for targeting, especially in minimizing exclusion errors. By using Chi-square Automatic Interaction Detection (CHAID) in 35 priority districts for handling extreme poverty, this study finds that the dependency ratio on households is the predictor variable that has the strongest interaction with extreme poverty status. Furthermore, the estimation results using the ordinal logistic regression model confirmed that the dependency ratio had a statistically significant effect on extreme poverty with a marginal effect value of 0.072. An additional one point in the value of the dependency ratio will increase the chance of experiencing extreme poverty by 7.2 percentage points